Analisis Profitabilitas, Makro Ekonomi dan Struktur Modal Terhadap Nilai Perusahaan pada Perusahaan Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023. - Shofi Putri Julian; Gustaf Naufan Febrianto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to test partially and simultaneously the effect of profitability, macroeconomics and capital structure on the value of textile and garment companies listed on the Indonesia Stock Exchange for the period 2019-2023. This study has a population of 22 textile and apparel companies and 10 companies were selected using the purposive sampling method. The type of research used is quantitative and the location of the research and sources can be seen at www.idx.co.id and www.bi.go.id. The analysis technique used is multiple linear regression analysis whose calculations are supported by SPSS statistical software, with a significance level of 0.05 or 5%. Based on the analysis using multiple linear regression which also answers the hypothesis by concluding that the results of the T-test (partial) of the profitability and macroeconomic variables have an effect but are not significant on the value of the company, while the capital structure of the company is significant to the value of the company. The F test (simultaneous) shows that the three variables together have a positive and significant effect on the value of the company.